KORELASI ANTARA KEBIASAAN MEMBACA DENGAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS VIII SMP NEGERI 1 RAMBAH - -, Ismail (Edu Research, 2016)
The research was conducted in SMP Negeri 1 Rambah. The method used in this study is correlational analysis method. This method is used to prove the presence or absence of relationship problems examined in class VIII SMP Negeri 1 Rambah. Thepurpose of this study was to determine the correlation between the habit of reading with reading comprehension class VIII SMP Negeri 1 Rambah. From this research is that in reading habit and reading comprehension class VIII SMP Negeri 1 Rambah,the average level of the reading habits of students is high, with an average score of 72.88. Similarly, the ability of students' reading comprehension is high with anaverage score of 73.4.